Interleukin-33-activated basophils promote asthma by regulating Th2 cell entry into lung tissue - Schuijs, Martijn J.; Brenis Gomez, Claudia M.; Bick, Fabian; Van Moorleghem, Justine; Vanheerswynghels, Manon; van Loo, Geert; Beyaert, Rudi; Vöhringer, David; Locksley, Richard M.; Hammad, Hamida; Lambrecht, Bart N. (Journal of Experimental Medicine, 2024)
Asthma is characterized by lung eosinophilia, remodeling, and mucus plugging, controlled by adaptive Th2 effector cells secreting IL-4, IL-5, and IL-13. Inhaled house dust mite (HDM) causes the release of barrier epithelial cytokines that activate various innate immune cells like DCs and basophils that can promote Th2 adaptive immunity directly or indirectly. Here, we show that basophils play a crucial role in the development of type 2 immunity and eosinophilic inflammation, mucus production, and bronchial hyperreactivity in response to HDM inhalation in C57Bl/6 mice. Interestingly, conditional depletion of basophils during sensitization did not reduce Th2 priming or asthma inception, whereas depletion during allergen challenge did. During the challenge of sensitized mice, basophil-intrinsic IL-33/ST2 signaling, and not FcεRI engagement, promoted basophil IL-4 production and subsequent Th2 cell recruitment to the lungs via vascular integrin expression. Basophil-intrinsic loss of the ubiquitin modifying molecule Tnfaip3, involved in dampening IL-33 signaling, enhanced key asthma features. Thus, IL-33-activated basophils are gatekeepers that boost allergic airway inflammation by controlling Th2 tissue entry.
CRIS-Team Scopus Importer:2024-10-04